Efektivitas Pekan Kreativitas Mahasiswa dalam Mewujudkan Nilai Islami dan Toleransi - Maulana Ibrahim; Zulkarnain Abdurrahman; M. Abel Radifan Rifki; Fara Audina Lubis; Rahayu Wulandari; Riska Aulia Firdanti; Zahwa Nazhifah Limbeng; Henrico Pinanda Ramadhan; Billy Prasetyo (Pusat Riset dan Inovasi Nasional, 2025)
Students, as agents of change, play a significant role in instilling Islamic values and tolerance in a diverse society. One of the ways to implement these values is through the Student Creativity Week, which involves various educational, innovative, and collaborative activities. This study aims to analyze the effectiveness of the Student Creativity Week in realizing Islamic values and tolerance in Manik Maraja Village. The research uses a descriptive qualitative approach, involving the community participatively in the planning, implementation, and evaluation stages. The results show that the Student Creativity Week successfully enhanced religious understanding among the youth, strengthened social solidarity, and fostered an inclusive attitude among residents. This program proved to be effective in building harmonious relationships among villagers and creating a more tolerant environment. Therefore, the Student Creativity Week program can be a collaborative community service model, with potential to be replicated in other villages to achieve sustainable social harmony.